Comparison of Polypropylene Flow Index to Increase Injection Efficiency In Plastic Injection Mold, 2 Cavities of Different Shapes Plastic (Case Study : Pencil Box) - Phongphattarawut, Worapong; Muparang, Supatthra; Wasanbongngem, Noppharit; Nithikarnjanatharn, Jittiwat; Nutkhum, Wannisa (RMUTL Engineering Journal, 2024)
This research used a computer program to simulate the flow, experimental design and statistical analysis to find the right parameters and properties of polypropylene to fix the problem of the injection of molded plastic with two cavities, when the shape is different and the time to fill a minimum of two different indicators to the cavities. The results of the experiment; plastic polymer polypropylene grade RJ6420 is more suitable for forming injection molded plastic pencil boxes than grade RP348S due to the flow characteristics when observing and recording the time to fill the two cavities. And has filled different than 0.0097 seconds to molding. The real piece of work is complete.